Pendampingan Literasi Budaya Melalui Permainan Tradisional Di SDN Saptorenggo 2 Kabupaten Malang - amelia, Delora jantung; Muzakki , Abdurrohman (Universitas Nusantara PGRI Kediri, 2022)
Along with the times, nowadays students playing using gadgets have become commonplace, both in rural and urban areas, all using gadgets. Addiction to gadgets is not a new thing, plus during the covid-19 pandemic, gadgets are something that cannot be separated between students. Learning activities, which are usually carried out face-to-face during this pandemic, are carried out boldly so that they don't want gadgets to be very important. The solution that can be offered as an effort to introduce culture and increase interest in reading is through cultural literacy assistance through traditional games at SDN Saptorenggo 2, Malang Regency. One effort that can overcome the shift in development of the times is by introducing culture through the implementation of traditional games by adhering to cultural literacy. This activity involves collaboration with partners, namely SDN Saptorenggo 2 located in Malang Regency. In this mentoring activity, teachers are appointed by class I-VI teachers. Prior to the implementation of this activity, it is necessary to hold a coordination meeting first, then present a workshop and continue with the provision of literacy through traditional games. Cultural literacy is knowledge and understanding in understanding and regarding Indonesian culture as an identity. This assistance is very much needed because the literacy movement can restore traditional game culture. This activity also involves physical activity and is also difficult to apply in learning activities. Therefore, this service activity is very much needed at SDN Saptorenggo 2.